The Contributions of Updating in Working Memory Sub-Processes for Sight-Reading Music Beyond Age and Practice Effects - Herrero, Laura; Carriedo, Nuria (Frontiers in Psychology, 2019)
Music sight reading (SR), has been described as a complex task which involves the simultaneous reading of new non-rehearsed material and performance. Although practice related skill have revealed as the most significant predictor of SR, working memory (WM) processes have shown its relevance in the study of individual differences in SR. We aimed to determine how the updating in WM sub-processes of retrieval/transformation and substitution, could differentially contribute to SR when the effects of age and practice were controlled, and according to the difficulty of the SR tasks and the different indexes of performance measured (SR error, tempo maintenance, rhythmic accuracy, pitch accuracy, articulation accuracy and expressiveness). 131 music students of different ages and levels of instrument knowledge participated in the study. The results showed that whereas the efficiency in the retrieval/transformation sub-processes contributed to SR regardless of the difficulty of the SR tasks, the substitution sub-process also contributed to performance at sight but only in low demanding SR tasks. The results also showed all the updating sub-processes were engaged in SR regarding the proportion of error and rhythmic accuracy. However, both expressiveness and tempo maintenance seemed to be uniquely driven by efficiency in the retrieval/transformation sub-processes, whereas articulation accuracy relied on the efficiency to suppress irrelevant information from WM.